EFEKTIFITAS PROGRAM KELUARGA HARAPAN (PKH) DESA TALAN KECAMATAN BANUA LAWAS KABUPATEN TABALONG (JAPB, 2022)
The Family Hope Program (PKH) is a program that provides cash assistance to Very Poor Households (RTSM). The Family Hope Program (PKH) is given to Very Poor Households (RTSM) that meet the requirements set by the Ministry of Social Affairs of the Republic of Indonesia based on the Decree of the Coordinating Minister for People's Welfare as chairman of the Poverty Reduction Coordination Team, Number: 31/KEP/MENKO/ -KESRA/IX/2007 concerning "The Family Hope Program Control Team (PKH). The study's purpose was to determine and analyze: 1) the Family Hope Program (PKH) effectiveness in Talan Village, Banua Lawas sub-district, Tabalong Regency. 2) the factors that hinder the effectiveness of the Family Hope Program (PKH) in Talan Village, Banua Lawas sub-district, Tabalong Regency. The research used an interview technique with a sample of 5 people: Talan Village Officials, PKH Cadres and PKH beneficiaries. The results of the study indicate that the implementation of PKH in Talan Village, Banua Lawas sub-district, has been running with the existing provisions because it is supported by factors of targeting accuracy, the availability of facilities and assistance activities, and the benefits are felt directly by the community both in the field of poverty. With the assistance of PKH in poverty, it can at least help the economy of needy families. Keywords: Effectiveness, Family Hope Program